2020
DOI: 10.7759/cureus.11094
|View full text |Cite
|
Sign up to set email alerts
|

Resident Education During COVID-19 Pandemic: Effectiveness of Virtual Electroencephalogram Learning

Abstract: To explore effectiveness of alternative methods of neurology resident electroencephalogram (EEG) learning during COVID-19 pandemic due to social distancing requirements which caused disruption of traditional inperson teaching. Methods Virtual EEG learning was instituted using Zoom platform. Residents participated in live, interactive virtual sessions for eight weeks. A pre-test and post-test were administered and a survey was performed at the end of the project. Results Based on pre-test and post-test results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…In the UK, medical colleges also provided virtual learning 9 , however, a survey of nal year UK medical students, reported 77.3 % medical elective placements being cancelled with only 1.6% being replaced by formative online modules 10 . Similarly, at a postgraduate level residency training programs in Canada 11 , ACGME accredited residency programs in the US 12 and speciality residency programs like neurology 13 started relying on e-learning tools for continuing didactic lectures and providing training in skills and procedures. Our study has also shown the same trend with QU CMED and HMC moving from a predominantly face-to-face delivery of education to online learning albeit after a short break.…”
Section: Models Of Education and Perceptionsmentioning
confidence: 99%
“…In the UK, medical colleges also provided virtual learning 9 , however, a survey of nal year UK medical students, reported 77.3 % medical elective placements being cancelled with only 1.6% being replaced by formative online modules 10 . Similarly, at a postgraduate level residency training programs in Canada 11 , ACGME accredited residency programs in the US 12 and speciality residency programs like neurology 13 started relying on e-learning tools for continuing didactic lectures and providing training in skills and procedures. Our study has also shown the same trend with QU CMED and HMC moving from a predominantly face-to-face delivery of education to online learning albeit after a short break.…”
Section: Models Of Education and Perceptionsmentioning
confidence: 99%
“…At the University of Arkansas (USA), a small‐scale virtual EEG teaching project was created for trainees 6 . Most participating residents rated these virtual EEG sessions more accessible, interactive, and engaging than traditional in‐person EEG teaching 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, most of these efforts and research have been aimed at postgraduate students, with fewer teaching models or strategies aimed primarily at undergraduate students (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%